Bandgap engineering of hydrogenated a-SiC:H thin films for photoelectrochemical water splitting applications - del Carmen Mejia M. (2020)
Bandgap engineering of a-SiC:H thin films was carried out to assess the material light absorption without compromising its photoelectrochemical water splitting capabilities. The tailoring was performed by varying the hydrogen concentration in the semiconductor and by post-deposition isochronical annealing treatments from 100 ?C to 700 ?C. Bandgap values were obtained by fitting the fundamental absorption region of the absorption coefficient using three different models. Differences among bandgap values extracted by these methods and its correlation with the a-SiC:H structure, demonstrate that structural features, rather than a hydrogen rearrangement or depletion, would be responsible for annealing induced optical bandgap increment. These features are taking in advantage for the bandgap engineering of a-SiC:H without changing Si-C stoichiometry. Optical bandgap values for p-doped a-SiC:H samples gradually increased from 2.59 to 2.76 eV upon performing each annealing step until 600 ?C. Temperature at which an enhancement in the electric performance is observed. We believe, these results will help on the design of monolithic tandem solar cells for water splitting applications. © 2020 IOP Publishing Ltd Printed in the UK